A bismuth oxide nanosheet-coated electrospun carbon nanofiber film: a free-standing negative electrode for flexible asymmetric supercapacitors. Issue 42 (12th October 2016) - Li, Lu; Zhang, Xitian; Zhang, Zhiguo; Zhang, Mingyi; Cong, Lujia; Pan, Yu; Lin, Shuangyan
Abstract : The development of a negative electrode for supercapacitors is very critical for the next-generation of energy-storage devices while it remains a great challenge. Abstract : The development of a negative electrode for supercapacitors is very critical for the next-generation of energy-storage devices while it remains a great challenge. Herein, a flexible and free-standing nanocomposite electrode of Bi2 O3 -decorated electrospun carbon nanofibers (ESCNFs) was prepared via electrospinning technology and a simple solvothermal method. The electrochemical performance of the nanocomposite electrode was investigated. An asymmetric supercapacitor (ASC) device made of the ESCNF@Bi2 O3 negative electrode and CF@NiCo2 O4 positive electrode was developed. It achieved excellent electrochemical properties including high energy density, high power density, and outstanding cycling stability. Moreover, the ability to power light-emitting diodes also indicates the feasibility for practical use. This work holds great promise for developing next-generation supercapacitors with high energy density.